Réponses

2013-11-27T22:41:35+01:00
Bonsoir,

D = (-2x + 1) - (4x² + x - 5) + (6 - 5x² + 3x) - (-3 + x)

1) D = -2x + 1 - 4x² - x + 5 + 6 - 5x² + 3x + 3 - x

\boxed{D = -9x^2 - x + 15}


2) x = 2

D(2) = -9\times2^2 - 2 + 15\\\\D(2) = -9\times4 - 2 + 15\\\\D(2) = -36- 2 + 15\\\\D(2) = -23

x =  -1

D(-1)=-9\times(-1)^2 - (-1) + 15\\\\D(-1)=-9\times1 +1 + 15\\\\D(-1)=-9+1 + 15\\\\D(-1)=7


x = 1/3

D(\dfrac{1}{3})=-9\times(\dfrac{1}{3})^2 - \dfrac{1}{3} + 15\\\\D(\dfrac{1}{3})=-9\times\dfrac{1}{9} -\dfrac{1}{3} + 15\\\\D(\dfrac{1}{3})=-1-\dfrac{1}{3} + 15\\\\D(\dfrac{1}{3})=14-\dfrac{1}{3}\\\\D(\dfrac{1}{3})=\dfrac{42}{3}-\dfrac{1}{3}\\\\D(\dfrac{1}{3})=\dfrac{41}{3}